Nutritional status affects immune function and exacerbates the severity of pulmonary tuberculosis - Lu, Chunli; Xu, Yunyi; Li, Xueya; Wang, Min; Xie, Bei; Huang, Yaling; Li, Yan; Fan, Jiahua (Frontiers in Immunology, 2024)
Aim To comprehensively evaluate the association and impact of nutritional status and immune function on the severity of pulmonary tuberculosis (PTB). Methods This descriptive cross-sectional study involved 952 participants who were diagnosed with active PTB. Severe PTB involves three or more lung field infections based on chest radiography. Nutritional status was evaluated using various indicators, including body mass index (BMI), the nutritional risk screening score (NRS-2002), total protein (TP), prealbumin (PA), transferrin (TRF), and serum albumin (ALB) levels and the prognostic nutritional index (PNI). Immune dysfunction was defined as a CD4+ count <500 cells/µl or a CD4+/CD8+ ratio <1. Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) were also calculated. Multivariate logistic and generalized linear regression were used to assess the associations between nutritional status, immune function, the severity of PTB, and the number of infected lung fields, adjusting for age, sex, and diabetes. Mediation analysis was conducted to evaluate the extent to which immune function mediated the impact of nutritional status on the severity of PTB. Sensitivity analysis was performed to enhance the robustness of the results. Results Compared to those in the general PTB group, patients in the severe PTB group tended to be older men with diabetes. Higher nutritional risk, higher proportion of immune dysfunction and lower lymphocyte counts were observed in the severe group. BMI and the PNI were found to be protective factors, while PLR was identified as a risk factor for disease severity. Immune dysfunction and the PLR are mediators of the relationship between nutritional status and PTB severity. When BMI, the PNI, and the PLR were combined with traditional clinical indicators, these parameters showed promising diagnostic value, and the AUC reached 0.701 (95% CI: 0.668–0.734). Conclusion The findings suggest that nutritional status is significantly associated with the severity of PTB, and immune function mediates the effects of nutritional status on the severity of PTB. Maintaining adequate BMI, PNI levels, and immune function or reducing PLR levels helps reduce the risk of severe PTB.